Winning Design! LEGO MINDSTORMS NXT Design Patterns for Fun and Competition - Trobaugh, James; SpringerLink (Online service) (Berkeley, CA : Apress : Imprint: Apress, 2010)
Winning Design! LEGO Mindstorms NXT Design Patterns for Fun and Competition is about design that works. It’s about building with LEGO MINDSTORMS NXT for fun, for education, but especially for competition. Author James Trobaugh is an experienced coach and leader in the FIRST LEGO League. In this book, he shares his hard-won knowledge about design principles and techniques that contribute to success in robotics competitions. Winning Design! unlocks the secrets of reliable design using LEGO MINDSTORMS NXT. You’ll learn proven design patterns that you can employ for common tasks such as turning, pushing, and pulling. You’ll reduce and compensate for variation in performance from battery charge levels and motor calibration differences. You’ll produce designs that won’t frustrate you by not working, but that will delight you with their reliable performance in the heat of competition. Good design is about more than just the hardware. Software counts for a lot, and Winning Design! has you covered. You’ll find chapters on program design and organization with tips on effective coding and documentation practices. You’ll learn about master programs and the needed flexibility they provide. There’s even a section on presenting your robot and software designs to the judges. Winning Design! is the book you need if your involved in competitions such as FIRST LEGO League events. Whether coach, parent, or student, you’ll find much in this book to make your design and competition experience fun and memorable, and educational. Please note: the print version of this title is black & white; the eBook is full color.
Design Considerations -- Chassis Design -- Navigation -- Going Straight -- Consistent Turning -- Line Following and Detection -- Squaring Up -- Collision Detection -- Manipulation -- Passive Attachments -- Power Attachments -- Pneumatics -- Programming -- Master Programs -- Program Management -- Documentation and Presentation.
Keywords: Computer input-output equipment; Computers; Computer programming; Hardware and Maker; Computing Milieux; Programming Techniques